2019
DOI: 10.3389/fmars.2019.00563
|View full text |Cite
|
Sign up to set email alerts
|

DSi as a Tracer for Submarine Groundwater Discharge

Abstract: Submarine groundwater discharge (SGD) is an important source of nutrients and metals to the coastal ocean, affects coastal ecosystems, and is gaining recognition as a relevant water resource. SGD is usually quantified using geochemical tracers such as radon or radium. However, a few studies have also used dissolved silicon (DSi) as a tracer for SGD, as DSi is usually enriched in groundwater when compared to surface waters. In this study, we discuss the potential of DSi as a tracer in SGD studies based on a lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 115 publications
1
26
0
Order By: Relevance
“…Ra isotopes and 222 Rn have served as the most powerful tools for gauging the magnitude and mechanism of SGD because Ra isotopes and 222 Rn are chemically conservative in seawater and enriched in groundwater 2 , 39 41 . Although it has received less attention than radioisotope tracers, DSi is also a useful tracer for determining SGD when DSi is highly enriched in fresh groundwater and it shows a conservative behavior in coastal aquifers 28 , 29 . In this study, the concentrations of DSi in fresh groundwater showed the highest values in fresh groundwater samples and exhibited good negative linear correlations with salinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ra isotopes and 222 Rn have served as the most powerful tools for gauging the magnitude and mechanism of SGD because Ra isotopes and 222 Rn are chemically conservative in seawater and enriched in groundwater 2 , 39 41 . Although it has received less attention than radioisotope tracers, DSi is also a useful tracer for determining SGD when DSi is highly enriched in fresh groundwater and it shows a conservative behavior in coastal aquifers 28 , 29 . In this study, the concentrations of DSi in fresh groundwater showed the highest values in fresh groundwater samples and exhibited good negative linear correlations with salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have attempted to measure SGD using hydrological processes 26 , 27 , seepage measurements 4 , 9 , and geochemical tracers such as Ra isotopes 2 , 3 and 222 Rn 5 . In addition, dissolved silicon (DSi) can be used as a geochemical tracer for determining SGD when it shows a conservative behavior in coastal aquifers 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they exhibited higher concentrations of silicate, which is enriched in the island's freshwater lens. As silicate serves as a proxy for fresh water influence (Oehler et al, 2019), it is indicative for the exfiltration of brackish porewater at the beach. The site specific orientation within the PCA is best defined for the October campaign.…”
Section: Geochemical Porewater Composition Reflects the Heterogeneitymentioning
confidence: 99%
“…Numerous methods have been used to detect and quantify SGD (Burnett et al, 2006) including optical systems (Karpen et al, 2004); geochemical water column investigations of tracers like the natural radionuclides radium and radon (Burnett & Dulaiova, 2003; Moore, 1996; Moore et al, 2008; Scholten et al, 2013), dissolved silicon (Oehler et al, 2019), methane, and chloride (Dulaiova et al, 2010; Schlüter et al, 2004); remote sensing (Shaban et al, 2005; Tamborski et al, 2015; Wilson & Rocha, 2012); and direct investigations using cores and different types of seepage meters (Bugna et al, 1996; Burnett & Dulaiova, 2003; Cable et al, 1997; Sauter et al, 2001). Only a few geophysical methods, like geoelectric (Stieglitz, 2005; Viso et al, 2010), controlled source electromagnetic (Gustafson et al, 2019; Müller et al, 2011), or autonomous underwater vehicle investigations (Sauter et al, 2003) have been used to explore SGD.…”
Section: Introductionmentioning
confidence: 99%